Kesinambungan Dan Tantangan Ukiran Kayu Palembang Dari Masa Kesultanan Hingga Modern - Husni Mubarat; Mukhsin Patriansah; Maslia (UNIVERSITAS INDO GLOBAL MANDIRI, 2025)
The existence of Palembang wood carvings began to be recorded since the era of the Palembang Darussalam Sultanate in the 14th century, which can be seen from the field of traditional Palembang architecture, namely the Limas House, namely in the furniture or household furnishings and mosque buildings such as pulpits and calligraphy. The ups and downs of the development of Palembang wood carvings are closely related to various social, economic, cultural, and religious factors that influence them, including modern culture. The urgency of the problem of this study is that wood carvings as one of Palembang's distinctive cultural heritages, until now have not received much attention from academics or intellectuals and also the government. The method used is the historical research method with data collection techniques that will be carried out through observation, interviews, literature studies and documentation studies. The data analysis process is carried out structurally and systematically starting from data identification, data reduction, data presentation and drawing conclusions. This research aims to explore wood carvings as a medium of expression as well as a culture that reflects the journey of history that influences identity and its journey to the present. through this research, it is expected to be able to provide references and also motivation for academics and art researchers to study the art of Palembang wood carving, so that this heritage is not only maintained physically, but also intellectually.